Regulation of Adipose-Derived Stem Cell Activity by Melatonin Receptors in Terms of Viability and Osteogenic Differentiation - Aleksandra Skubis-Sikora; Bartosz Sikora; Weronika Małysiak; Patrycja Wieczorek; Piotr Czekaj (MDPI AG, 2023)
Melatonin is a hormone secreted mainly by the pineal gland and acts through the Mel1A and Mel1B receptors. Among other actions, melatonin significantly increases osteogenesis during bone regeneration. Human adipose-derived mesenchymal stem cells (ADSCs) are also known to have the potential to differentiate into osteoblast-like cells; however, inefficient culturing due to the loss of properties over time or low cell survival rates on scaffolds is a limitation. Improving the process of ADSC expansion in vitro is crucial for its further successful use in bone regeneration. This study aimed to assess the effect of melatonin on ADSC characteristics, including osteogenicity. We assessed ADSC viability at different melatonin concentrations as well as the effect on its receptor inhibitors (luzindole or 4-P-PDOT). Moreover, we analyzed the ADSC phenotype, apoptosis, cell cycle, and expression of MTNR1A and MTNR1B receptors, and its potential for osteogenic differentiation. We found that ADSCs treated with melatonin at a concentration of 100 µM had a higher viability compared to those treated at higher melatonin concentrations. Melatonin did not change the phenotype of ADSCs or induce apoptosis and it promoted the activity of some osteogenesis-related genes. We concluded that melatonin is safe, non-toxic to normal ADSCs in vitro, and can be used in regenerative medicine at low doses (100 μM) to improve cell viability without negatively affecting the osteogenic potential of these cells.